PELATIHAN TARI PERSEMBAHAN MENGGUNAKAN MEDIA VIDEO UNTUK MENINGKATKAN KETERAMPILAN GERAK TARI SISWA BERKEBUTUHAN KHUSUS - Dwi Anggraini; Hasnawati Hasnawati; Yusnia Yusnia (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2023)
Training and Assistance Activities of Persembahan Dance Using Video Media to Improve the Dance Movement Skills of Special School Students (SLB) "Amal Mulia" Bengkulu aims to improve students' dance movement skills using video learning media for Persembahan Dance and Silat Pedang. The implementation method is in the form of training which consists of planning, implementing training and mentoring and evaluating activities. The instrument used to measure students' movement skills is a questionnaire given during the activity. Training and mentoring was carried out for 2 days and independent training was carried out 3 times accompanied by a companion teacher from SLM Amal Mulia. The training was carried out by showing video tutorials on the Persembahan Dance and Silat Pedang. During independent practice at school, the teacher sends an exercise video to get an evaluation from the PPM team. Based on the results of the activity, the students' movement skills increased at each practice time. The average student movement skills per aspect are 95% wiraga, 95% wirasa, 89% wirama and 83% harmonization. Based on the data collected, it can be concluded that training and mentoring of offering dances using video media can improve the movement skills of "Amal Mulia" SLB students.